Welding of T-joint configuration between dissimilar metals using low powered fiber laser / Shamini P. Janasekaran - Shamini, P. Janasekaran (2017)
Welding is a fabrication process of joining two different parts together and in some welding process it involves heat transmission between two metals to get strong joint. Welding process can be divided into two categories, which are fusion welding and solid state welding processes. The drawbacks of these fusion methods are welding can damage the surface of the materials and need precise techniques with skilled and trained operators. Laser beam welding technique was established on high power laser machine which requires high capital cost and investment. However, with the advancement of fiber laser technology, there is possibility of using low power fiber laser welding to weld dissimilar metals. In this research, low power fiber laser welding were used to weld T-joint on dissimilar metals. A fuzzy logic model was developed from the training data and validated with testing data from pull test results to select parameter range for further metallurgical and microhardness analysis. In preliminary study, dissimilar aluminum alloys of AA2024-O acted as skin and AA7075-T6 acted as stringer were welded double-sided to evaluate the joining capability. The influences of laser welding speed and focal distances for constant laser power, 270 W were studied to determine the weldment penetration in this study. It was found that full penetration was obtained at welding speed 9mm/s with the highest heat input approximately 4715 J/mm needs 642.79N to break the joints. The microstructural analysis proved the formation of smaller grain sizes due to laser welding. Vickers microhardness did not show improvement in weldment hardness and filler alloy, BA4047 was added to evaluate its influence to mechanical properties. For the same parameters, the fracture force and Vickers microhardness increased approximately 300% and 1200% respectively when filler alloy was added. Single sided laser welding has advantage for inaccessible seam welding. Titanium base alloy, Ti6Al4V as skin and nickel base alloy, Inconel 600 as stringer were welded in T joint configuration using same technique. Overlapping factor and welding speed were studied and the effects were examined. The maximum force, 150N needed to fracture the welded sample when the overlapping factor was 50% and the welding speed was 40 mm/s at a given constant power of 250W. Microhardness has increased 200% from base metals with formation of intermetallic compound, NiTi and NiTi2 formed at fusion zone from the Energy Dispersive X-Ray Spectroscopy and X-ray diffraction analysis. Overall, double sided and single sided laser welding was possible using low power fiber laser to form a sound weldment.